Transfer of a Redox-Signal through the Cytosol by Redox-Dependent Microcompartmentation of Glycolytic Enzymes at Mitochondria and Actin Cytoskeleton - Wojtera-Kwiczor, Joanna; Gross, Felicitas; Leffers, Hans-Martin; Kang, Minhee; Schneider, Markus; Scheibe, Renate (Frontiers in Plant Science, 2013)
The cytosolic glyceraldehyde-3-phosphate dehydrogenase (GAPDH, EC 1.2.1.12, GapC) plays an important role in glycolysis by providing the cell with ATP and NADH. Interestingly, despite its glycolytic function in the cytosol, GAPDH was reported to possess additional non-glycolytic activities, correlating with its nuclear, or cytoskeletal localization in animal cells. In transiently transformed mesophyll protoplasts from Arabidopsis thaliana colocalization and interaction of the glycolytic enzymes with the mitochondria and with the actin cytoskeleton was visualized by confocal laser scanning microscopy (cLSM) using fluorescent protein fusions and by bimolecular fluorescence complementation, respectively. Yeast two-hybrid screens, dot-blot overlay assays, and co-sedimentation assays were used to identify potential protein–protein interactions between two cytosolic GAPDH isoforms (GapC1, At3g04120; GapC2, At1g13440) from A. thaliana with the neighboring glycolytic enzyme, fructose 1,6-bisphosphate aldolase (FBA6, At2g36460), the mitochondrial porin (VDAC3; At5g15090), and actin in vitro. From these experiments, a mitochondrial association is suggested for both glycolytic enzymes, GAPDH and aldolase, which appear to bind to the outer mitochondrial membrane, in a redox-dependent manner. In addition, both glycolytic enzymes were found to bind to F-actin in co-sedimentation assays, and lead to bundling of purified rabbit actin, as visualized by cLSM. Actin-binding and bundling occurred reversibly under oxidizing conditions. We speculate that such dynamic formation of microcompartments is part of a redox-dependent retrograde signal transduction network for adaptation upon oxidative stress.